A software architecture for mechanism-based social systems modelling in agent-based simulation models - Vu, Tuong Manh; Probst, Charlotte; Nielsen, Alexandra; Bai, Hao; Buckley, Charlotte; Meier, Petra S.; Strong, Mark; Brennan, Alan; Purshouse, Robin C. (The journal of artificial societies and social simulation, 2020)
This paper introduces the MBSSM (Mechanism-Based Social Systems Modelling) software architecture that is designed for expressing mechanisms of social theories with individual behaviour components in a unified way and implementing these mechanisms in an agent-based simulation model. The MBSSM architecture is based on a middle-range theory approach most recently expounded by analytical sociology and is designed in the object-oriented programming paradigm with Unified Modelling Language diagrams. This paper presents two worked examples of using the architecture for modelling individual behaviour mechanisms that give rise to the dynamics of population-level alcohol use: a single-theory model of norm theory and a multi-theory model that combines norm theory with role theory. The MBSSM architecture provides a computational environment within which theories based on social mechanisms can be represented, compared, and integrated. The architecture plays a fundamental enabling role within a wider simulation model-based framework of abductive reasoning in which families of theories are tested for their ability to explain concrete social phenomena.
Gesehen am 28.07.2020